(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The 5-Mercapto-3-(2-thienyl)-s-triazole having different biological activities were prepared in high yield using Mont.K-10, KSF under microwave conditions which causes no pollution, reduces the reaction time, provide uniform heating of reaction material and becomes a part of green chemistry by counteracting against the conventional heating methods in Brown chemistry.